Human values in curating a human rights media archive - Durrant, Abigail; Kirk, Dave; Reeves, Stuart (ACM, 2014)
Cultural institutions, such as museums, often curate politically and ethically sensitive materials. Increasingly, Internet-enabled, digital technology intersects with these curatorial practices offering new opportunities for public and scholarly engagement. We report on a case study of human rights media archiving at a genocide memorial centre in Rwanda, motivated by interests in ICT support to memorialisation practices. Through an analysis of our discussions with staff about their work, we report on how accounts of the Rwandan Genocide are being captured and curated to support the centre's humanitarian agenda and associated values. We identify transferable curatorial concerns for human rights media communication amongst scholarly networks and public audiences worldwide, elucidating interaction design challenges for supportive ICT and contributing to HCI discourses on value sensitive design and cultural engagement with sensitive materials.